Application of drug–metal ion interaction principle in conductometric determination of imatinib, sorafenib, gefitinib and bosutinib - Alhazmi Hassan A.; Ali Bokar Nasib AbdulRhman; Musleh Yasser Ali; Hijri Khaled Qassim; Rehman Zia ur; Khuwaja Gulrana; Al-Bratty Mohammed; Javed Sadique A.; Arbab Ismail A. (Open Chemistry, 2020)
An analytical method for the quantification of anticancer agents such as imatinib, sorafenib, gefitinib and bosutinib using conductometry was developed. Each drug solution was mixed with measured concentration of metal ion (Cu2+) solution resulting in drug–metal ion complexation in the titration cell. Conductance was progressively decreased on addition of the analyte solution up to a point of maximum reduction, that is, the end point. Corrected conductance values were calculated from the observed conductance and used to plot a graph against the volume of drug solution added. No interferences were observed from blank and placebo as they gave no clear inflection in the conductivity during titration. The precision and the accuracy of the developed method was established by the analysis of quality control samples; %RSD of corrected conductance values <2% and recovery results within 100 ± 2% were achieved. The calibration graphs obtained were linear over the concentrations 1.0–1.4 mM for all the drugs (R 2 > 0.99). The drugs were successfully analyzed in their respective dosage forms prepared in-house. The method has offered easier, faster and cost-effective analysis of the selected drugs and can be used for routine determinations in the quality control laboratories. More importantly, it is an environmental friendly procedure, as no organic solvent was used throughout the analysis.